Brussels youth: between diversity and adversity - Dirk Jacobs; Andrea Rea (Brussels Studies, 2007)
Brussels is a city which is highly segmented on both the social as the cultural level. This diversity is also reflected among the youth. In this article we present the results of a survey undertaken among the last year students of the francophone schools of the city of Brussels. The survey, which focusses on life styles, racism and insecurity, confirms the multifaceted character of the Brussels youth. Important sources of diversity and division are social background, ethnic origin and school choice. Our findings attest that the relations amongst young people are built on identities that are rooted in references to socio-economic class and ethnic origin, while their intensity varies with the type of education. The ethnicisation of the young people’s social relations seems to be very widespread. The survey attests to a paradox: racist insults are quite common, and are not only oriented towards ethnic minorities, but at the same time almost everyone supports the dominant antiracist discourse.